Implementasi Literasi Digital Guru SD Melalui Pendampingan Pembuatan Digital Material (Sway) - Kuncahyono Kuncahyono; Maharani Putri Kumalasani (STKIP Singkawang, 2020)
The purpose of this service is to assist partners in improving digital literacy skills and teacher competencies at SDN Juwet 2 Kab. Kediri is one of the efforts to implement digital-based learning that can be used as online learning teaching materials. This research method uses a participatory action research (PAR) approach. The method of this activity is carried out based on research by 1) conducting socialization and workshops on digital material and digital literacy, 2) compiling digital material (sway) based on the internet, 3) implementing digital material products (sway) in online learning. The results of this research-based activity produce digital material (sway) products that can be used as online teaching materials. Second, the results of the pre-test and post-test show that the digital literacy skills of teachers have increased. The final result shows that the final product of making digital material is a digital material product (sway) which can be used as teaching material implemented in the online learning process with students